Gold nanoparticle decoration potentiate the antibacterial enhancement of TiO2 nanotubes via sonodynamic therapy against peri-implant infections - Sun, Yue; Xu, Wenzhou; Jiang, Cong; Zhou, Tianyu; Wang, Qiqi; A, Lan (Frontiers in Bioengineering and Biotechnology, 2022)
Inflammatory damage from bacterial biofilms usually causes the failure of tooth implantation. A promising solution for this challenge is to use an implant surface with a long-term, in-depth and efficient antibacterial feature. In this study, we developed an ultrasound-enhanced antibacterial implant surface based on Au nanoparticle modified TiO2 nanotubes (AuNPs-TNTs). As an artificial tooth surface, films based on AuNPs-TNTs showed excellent biocompatibility. Importantly, compared to bare titania surface, a larger amount of reactive oxygen radicals was generated on AuNPs-TNTs under an ultrasound treatment. For a proof-of-concept application, Porphyromonas gingivalis (P. gingivalis) was used as the model bacteria; the as-proposed AuNPs-TNTs exhibited significantly enhanced antibacterial activity under a simple ultrasound treatment. This antibacterial film offers a new way to design the surface of an artificial implant coating for resolving the bacterial infection induced failure of dental implants.